Accumulation of 137Cs by herbaceous plants on peat-bog soils in the West Polissya of Ukraine - I. M. Maloshtan; S. V. Polishchuk (Ядерна фізика та енергетика)
Levels of 137Cs accumulation by herbaceous plants on peat-bog soils lands of the Stare Selo settlement of Rokytne district of Rivne region were investigated 31 years after the Chernobyl accident. Data on terrestrial contamination density with 137Cs and vertical distribution of 137Cs in soil profiles are presented. 137Cs accumulation coefficients and transfer factors from peat-bog soils to dominant species of herbaceous plants were determined. Differences of 137Cs accumulation by herbaceous plants depending on the development stage and vegetative period were revealed. Forecast of milk contamination with 137Cs was made under the application of meadow grasslands as the feed on the investigated territory of fodder lands.